Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure, let's evaluate the given expression step-by-step for both sets of values.
The expression we need to evaluate is:
[tex]\[ \frac{x}{3} + 3y^2 + 1 \][/tex]
Let's start with the first set of values: [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex].
### Evaluation when [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex]:
1. Substitute [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex] into the expression:
[tex]\[ \frac{21}{3} + 3(-2)^2 + 1 \][/tex]
2. Calculate [tex]\(\frac{21}{3}\)[/tex]:
[tex]\[ \frac{21}{3} = 7 \][/tex]
3. Calculate [tex]\(3(-2)^2\)[/tex]:
[tex]\[ (-2)^2 = 4 \quad \Rightarrow \quad 3 \times 4 = 12 \][/tex]
4. Add the results of the individual calculations:
[tex]\[ 7 + 12 + 1 = 20 \][/tex]
So, the value of the expression when [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex] is [tex]\(\boxed{20.0}\)[/tex].
### Evaluation when [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex]:
1. Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex] into the expression:
[tex]\[ \frac{3}{3} + 3(4)^2 + 1 \][/tex]
2. Calculate [tex]\(\frac{3}{3}\)[/tex]:
[tex]\[ \frac{3}{3} = 1 \][/tex]
3. Calculate [tex]\(3(4)^2\)[/tex]:
[tex]\[ (4)^2 = 16 \quad \Rightarrow \quad 3 \times 16 = 48 \][/tex]
4. Add the results of the individual calculations:
[tex]\[ 1 + 48 + 1 = 50 \][/tex]
So, the value of the expression when [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex] is [tex]\(\boxed{50.0}\)[/tex].
In conclusion, the evaluated expressions are:
- For [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex], the result is [tex]\(20.0\)[/tex].
- For [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex], the result is [tex]\(50.0\)[/tex].
The expression we need to evaluate is:
[tex]\[ \frac{x}{3} + 3y^2 + 1 \][/tex]
Let's start with the first set of values: [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex].
### Evaluation when [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex]:
1. Substitute [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex] into the expression:
[tex]\[ \frac{21}{3} + 3(-2)^2 + 1 \][/tex]
2. Calculate [tex]\(\frac{21}{3}\)[/tex]:
[tex]\[ \frac{21}{3} = 7 \][/tex]
3. Calculate [tex]\(3(-2)^2\)[/tex]:
[tex]\[ (-2)^2 = 4 \quad \Rightarrow \quad 3 \times 4 = 12 \][/tex]
4. Add the results of the individual calculations:
[tex]\[ 7 + 12 + 1 = 20 \][/tex]
So, the value of the expression when [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex] is [tex]\(\boxed{20.0}\)[/tex].
### Evaluation when [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex]:
1. Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex] into the expression:
[tex]\[ \frac{3}{3} + 3(4)^2 + 1 \][/tex]
2. Calculate [tex]\(\frac{3}{3}\)[/tex]:
[tex]\[ \frac{3}{3} = 1 \][/tex]
3. Calculate [tex]\(3(4)^2\)[/tex]:
[tex]\[ (4)^2 = 16 \quad \Rightarrow \quad 3 \times 16 = 48 \][/tex]
4. Add the results of the individual calculations:
[tex]\[ 1 + 48 + 1 = 50 \][/tex]
So, the value of the expression when [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex] is [tex]\(\boxed{50.0}\)[/tex].
In conclusion, the evaluated expressions are:
- For [tex]\(x = 21\)[/tex] and [tex]\(y = -2\)[/tex], the result is [tex]\(20.0\)[/tex].
- For [tex]\(x = 3\)[/tex] and [tex]\(y = 4\)[/tex], the result is [tex]\(50.0\)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.